Associations between male testosterone and immune function in a pathogenically stressed forager‐horticultural population. Issue 3 (28th July 2016) - Trumble, Benjamin C.; Blackwell, Aaron D.; Stieglitz, Jonathan; Thompson, Melissa Emery; Suarez, Ivan Maldonado; Kaplan, Hillard; Gurven, Michael
Abstract: Objectives: Despite well‐known fitness advantages to males who produce and maintain high endogenous testosterone levels, such phenotypes may be costly if testosterone‐mediated investment in reproductive effort trade‐off against investment in somatic maintenance. Previous studies of androgen‐mediated trade‐offs in human immune function find mixed results, in part because most studies either focus on a few indicators of immunity, are confounded by phenotypic correlation, or are observational. Here the association between male endogenous testosterone and 13 circulating cytokines are examined before and after ex vivo antigen stimulation with phytohemagglutinin (PHA) and lipopolysaccharides (LPS) in a high pathogen population of Bolivian forager‐horticulturalists. Materials and methods: A Milliplex 13‐plex cytokine panel measured cytokine concentration in whole blood samples from 109 Tsimane men aged 40–89 (median = 50 years) before and after antigen stimulation with PHA and LPS. Urinary testosterone was measured via enzyme immunoassay, demographic, and anthropometric data were collected as part of the Tsimane Health and Life History Project. Results: Higher endogenous testosterone was associated with down‐regulated responses in all cytokines after PHA stimulation (but significantly in only 2/13 cytokines), controlling for age and body mass index. In contrast, testosterone was not significantly associated with down‐regulation of cytokines after LPS stimulation. MANOVAs indicate that men with higher testosterone showed reduced cytokine responses to PHA compared with LPS ( p  = 0.0098). Discussion: Endogenous testosterone appears to be immunomodulatory rather than immunosuppressive. Potentially costlier forms of immune activation like those induced by PHA (largely T‐cell biased immune activation) are down‐regulated in men with higher testosterone, but testosterone has less impact on potentially less costly immune activation following LPS stimulation (largely B‐cell mediated immunity).